Perception of education in medical interview, physician patient relationship and communication skills. Survey of medical graduates - Sogi, Cecilia (2007)
Objective. To identify factors associated to medical interview, physician-patient relationship and communication skills of medical graduates Design: Survey type study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Medical graduates. Methods: Data base of a survey to medical graduates on their training in core clinical skills was used. Main outcome measures: Medical interview, physician patient relatioship and communication skills. Results: The data base was obtained from 917 graduates, 59 % male, 56% between 25-29 years old. A quarter was graduated from the Universidad Nacional Mayor de San Marcos, one third graduated in 2003; 85% responded that they had been trained in core clinical skills. The highest score in clinical skills was related to have had training in those skills in bi and multivariate analysis and to be graduated before 2003, in multivariate analysis. Two third of the comments showed positive attitudes towards this type of study. Conclusions: Clinical practice requires training in clinical skills likewise years of clinical experience, according to the perception of the graduates.